Electrospun silica nanofiber mats functionalized with ceria nanoparticles for water decontamination. Issue 34 (20th June 2019) - Zucker, Ines; Dizge, Nadir; Fausey, Camrynn L.; Shaulsky, Evyatar; Sun, Meng; Elimelech, Menachem
Abstract : This study demonstrates the fabrication of nanoceria-immobilized silica nanofibers for efficient water decontamination with easy reuse and regeneration properties. Abstract : This study demonstrates the fabrication of nanoceria-immobilized silica nanofibers for efficient water decontamination with easy reuse and regeneration properties. Commercially-available ceria (CeO2 ) nanoparticles were immobilized on electrospun silica nanofiber mats. Optimal conditions for both oxidation of model trace organic compounds (TrOCs) and hydroxyl-radical formation were determined in batch experiments with ceria nanoparticles. Kinetic experiments showed comparable oxidation rates of positively- and neutrally-charged TrOCs (95 and 98%, respectively) by the nanofiber composites at pH 2 in 0.5 mM H2 O2 . We demonstrated the reuse properties of the ceria nanofiber composites, finding less than a 15% reduction in oxidation performance after 10 cycles. In addition to this oxidative performance, the electrospun CeO2 nanofiber composites are also applicable for adsorbing the persistent contaminant perfluorooctanesulfonic acid (PFOS) through electrostatic interactions. Regeneration of the fibers was enabled through a one-hour heat treatment at 550 °C in air. Overall, results from this study show that the nanoceria-immobilized silica nanofibers can be used as efficient oxidative and adsorptive media to treat TrOCs in acidic waters, without use of an additional catalyst separation stage from solution.